2013
DOI: 10.1245/s10434-013-3395-6
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Radiotherapy for Malignant Phyllodes Tumors: Analysis of the National Cancer Data Base, 1998–2009

Abstract: Utilization of adjuvant radiotherapy for malignant phyllodes doubled from 1998 to 2009. Radiotherapy significantly reduced LR but had no effect on DFS or OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 33 publications
0
73
1
3
Order By: Relevance
“…This is similar to trends previously reported by Gnerlich et al using the National Cancer Data Base (NCDB). 14 Currently, there are no randomized controlled trials that have examined the efficacy of XRT after margin-negative surgery for phyllodes tumors; however, the relatively high rate of local recurrence (LR) has generated interest in the potential role of XRT. There have been several retrospective studies examining the impact of XRT on local recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to trends previously reported by Gnerlich et al using the National Cancer Data Base (NCDB). 14 Currently, there are no randomized controlled trials that have examined the efficacy of XRT after margin-negative surgery for phyllodes tumors; however, the relatively high rate of local recurrence (LR) has generated interest in the potential role of XRT. There have been several retrospective studies examining the impact of XRT on local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these single institution experiences are mixed however. 1,2,9,10,12,14 A retrospective study by Belkacemi et al evaluated 446 patients treated for phyllodes tumors with a 45% negative margin rate between 1971 and 2003. Adjuvant XRT was administered to 38 (8.5%) patients and they reported a significant decrease in 10 year LR rates from 86% to 56%.…”
Section: Discussionmentioning
confidence: 99%
“…However, application of radiotherapy to the breast after surgery for borderline and malignant PTs was shown to reduce the risk of local recurrence, without any significant survival benefit (27,28). Therefore, adjuvant radiotherapy should be considered in patients with borderline and malignant PT on an indidualized basis (4,5).…”
Section: Fnac: Fine Needle Aspiration Cytologymentioning
confidence: 99%
“…Despite a nationwide breast cancer screening program and public awareness activities, it is still not uncommon to see women presenting with large advanced tumours in Singapore [21]. Several authors have found radiation to reduce local recurrence rates, but unlike with the usual invasive breast cancers, radiation did not improve survival in malignant phyllodes [22][23][24].…”
Section: Discussionmentioning
confidence: 99%